The Atlantic Ghost Crab Ocypode quadrata (Decapoda: Ocypodidae) as bioindicator of sandy beaches: assessment of the influence of environmental, behavioral and population factors - Pombo, Maíra (2015)
The populations of the ghost-crab Ocypode quadrata have been evaluated as bioindicators at sandy beaches, but for this purpose some shortcomings need to be addressed. This study assessed several features of the species biology, from daily activity cycles to effectively its role as bioindicator. Between that, the occupation of burrows was evaluated at several morphodymically distinct beaches and it differed temporally, among the areas and within beach strata, indicating that assessing these populations through the indirect method require more caution. The period of the year after major cold fronts showed the most similar values between individuals and burrows, followed by the greater entrance of young recorded. No trend according to beach type was identified for mean size, dissipative beaches tended to have higher densities, while body growth performance index was higher at reflective beaches, gathering therefore both similarities and differences concerning the trends known for other crustaceans from these environments. The use of the species as bioindicator was effective and gathered distinct areas, through the use of a new method. Increasing levels of erosion were associated to increasing mean densities and mean sizes, followed by a sharp decrease of both, especially mean size. Connectivity breakage, e.g., armoring and vegetation removal, proved to be a threat to the populations structure, worsened when associated to erosion process, to an extent that compromise the populations viability.